Insights on Hydrothermal‐Magmatic Interactions and Eruptive Processes at Poás Volcano (Costa Rica) From High‐Frequency Gas Monitoring and Drone Measurements. Issue 3 (6th February 2019) - de Moor, J. M.; Stix, J.; Avard, G.; Muller, C.; Corrales, E.; Diaz, J. A.; Alan, A.; Brenes, J.; Pacheco, J.; Aiuppa, A.; Fischer, T. P.
Abstract: Identification of unambiguous signals of volcanic unrest is crucial in hazard assessment. Processes leading to phreatic and phreatomagmatic eruptions remain poorly understood, inhibiting effective eruption forecasting. Our 5‐year gas record from Poás volcano, combined with geophysical data, reveals systematic behavior associated with hydrothermal‐magmatic eruptions. Three eruptive episodes are covered, each with distinct geochemical and geophysical characteristics. Periods with larger eruptions tend to be associated with stronger excursions in monitoring data, particularly in SO2 /CO2 and SO2 flux. The explosive 2017 phreatomagmatic eruption was the largest eruption at Poás since 1953 and was preceded by dramatic changes in gas and geophysical parameters. The use of drones played a crucial role in gas monitoring during this eruptive period. Hydrothermal sealing and volatile accumulation, followed by top‐down reactivation of a shallow previously emplaced magma body upon seal failure, are proposed as important processes leading to and contributing to the explosivity of the 2017 eruption. Plain Language Summary: High‐frequency monitoring of phreatic eruptions shows that clear precursory signals often exist to these dangerous explosive events. We interrogate the processes that lead to phreatic eruptions and investigate the intricate connections between magma intrusions and the hydrothermal systems that they feed. Key Points: Three eruptive phases are characterized in detail through five years of high‐frequency monitoring We identify and discuss precursors to phreatic and phreatomagmatic eruptions Enhanced hydrothermal sealing can lead to larger eruptions and top‐down remobilization of magma